2019
DOI: 10.3389/fphar.2019.00166
|View full text |Cite
|
Sign up to set email alerts
|

Carbocisteine Improves Histone Deacetylase 2 Deacetylation Activity via Regulating Sumoylation of Histone Deacetylase 2 in Human Tracheobronchial Epithelial Cells

Abstract: Histone deacetylase (HDAC) 2 plays a vital role in modifying histones to mediate inflammatory responses, while HDAC2 itself is commonly regulated by post-translational modifications. Small ubiquitin-related modifier (SUMO), as an important PTM factor, is involved in the regulation of multiple protein functions. Our previous studies have shown that carbocisteine (S-CMC) reversed cigarette smoke extract (CSE)-induced down-regulation of HDAC2 expression/activity in a thiol/GSH-dependent manner and enhanced sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…It may promote fibroblast proliferation and collagen synthesis, inhibit collagen fiber decomposition and facilitate the deposition of extracellular matrix, the formation of granulation tissue and fibrosis ( 49 ). In human tracheobronchial epithelial cells, carbocisteine, which is a mucoactive drug, reduced IL-8 expression by increasing HDAC2 activity ( 50 ). Erythromycin may increase the activity of HDAC2 via inhibiting the PI3K/Akt pathway and reducing the release of inflammatory factors, such as IL-8, thereby increasing the anti-inflammatory activity of budesonide ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It may promote fibroblast proliferation and collagen synthesis, inhibit collagen fiber decomposition and facilitate the deposition of extracellular matrix, the formation of granulation tissue and fibrosis ( 49 ). In human tracheobronchial epithelial cells, carbocisteine, which is a mucoactive drug, reduced IL-8 expression by increasing HDAC2 activity ( 50 ). Erythromycin may increase the activity of HDAC2 via inhibiting the PI3K/Akt pathway and reducing the release of inflammatory factors, such as IL-8, thereby increasing the anti-inflammatory activity of budesonide ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…In human THP-1 cells stimulated with lipopolysaccharide and primary human peripheral blood mononuclear cells, pre-treatment with the HDAC inhibitor trichostatin A or gene silencing of HDAC1 and HDAC2 inhibited the anti-inflammatory effects of isoflurane and increased the expression of TNF-α, IL-8 and interleukin-1β ( 51 ). These studies indicated that increasing the expression/activity of HDAC2 reduces the release of the inflammatory factor IL-8 and enhances the anti-inflammatory effect, while inhibiting the expression/activity of HDAC2 increases the release of the inflammatory factor IL-8 and aggravates the inflammatory response ( 13 , 50 , 51 ). A clinical study revealed that mechanical damage, which was triggered via tracheal intubation induced an increased expression of TGF-β, VEGF, and basic fibroblast growth factor, which resulted in enhanced expression of collagen type I and III, tracheal granulation hyperplasia and tracheal stenosis ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CSE preparation was performed as previous described, with minor modifications [ 26 ]. Briefly, one cigarette (each cigarette: nicotine, 1.0 mg; tar oil, 10 mg; carbon monoxide, 13 mg; Tobacco Hunan Industrial Corporation, China) was combusted, and the smoke was passed through 10 mL of serum-free culture medium at a rate of 5 min/cigarette.…”
Section: Methodsmentioning
confidence: 99%
“…We analyzed the uorophore with the excitation at 360nm and emission at 460nm by using a uorescence plate reader. CSE preparation CSE preparation followed a previous report, with minor modi cations [23]. Brie y, one cigarette (per cigarette: nicotine, 1.0 mg; tar oil, 10 mg; carbon monoxide, 13 mg; Tobacco Hunan Industrial Corporation, China) was combusted, and the smoke was passed through 10 mL of serum-free culture medium at 5 min/cigarette.…”
Section: Hdac2 Activitymentioning
confidence: 99%